The Effect of Acceptance and Commitment Therapy on The Quality of Life of Post Stroke Patients in Aloei Saboe Hospital - Fatmawati Mohamad1, Wenny Ino Ischak1, Heni Panai1, Hafni Van Gobel1, Yusrin Aswad1, Rini Fahriani Z (Institute of Medico-legal Publications Pvt Ltd, 2020)
Quality of life is a global concept that emphasizes dimensions of health status including finance, housing, and work. The quality of life of post-stroke sufferers can experience disturbances or obstacles due to physical disabilities, cognition, psychological and social disorders. The purpose of this study was to determine the effect of ACT interventions on changes in the quality of life of post-stroke patients at Aloe Saboe Hospital. The method used in this research is quasi-experimental research method pre-posttest with the control group. The sampling technique used was the purposive sampling technique. The number of samples studied was 60 respondents divided into the experimental group (ACT Therapy and health education) and the control group (health education). The variables used are independent variables namely ACT therapy and the dependent variable is the quality of life of patients after stroke. Based on the results of the analysis, there is an effect of ACT intervention on improving quality of life in post-stroke patients as evidenced by the results of t count = -9.015, then the Significant value is 0,000. This shows that the value of p <0.05 then Ho is rejected, so the research hypothesis is proven that there is an effect of ACT therapy on the quality of life of post-stroke patients at Aloei Saboe Hospital, Gorontalo City.